Composite solid-state sodium battery electrolyte and method of making same

CN122267284BActive Publication Date: 2026-10-27HUNAN FENGRI ELECTRIC GROUP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610585365.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-29
Publication Date
2026-10-27
Estimated Expiration
2046-04-29

AI Technical Summary

Technical Problem

然而,NASICON陶瓷电解质的烧结温度偏高,容易导致钠挥发,且晶界电阻较高,与钠金属负极的界面兼容性差,限制了其应用

Benefits of technology

通过PCN-224、酒石酸锑钾、氟盐和钠补充剂的添加,结合优化的热处理工艺,实现了NASICON电解质性能的优化。PCN-224热解形成碳质/Zr氧化物多孔结构,促进物质传输与元素均匀扩散;酒石酸锑钾提供Sb源优化晶格结构,同时K源助熔降低烧结温度;氟盐实现氟取代和晶界改性,提升离子传导能力;草酸钠分解补充钠源并辅助形成连通孔隙结构。所得复合固态钠电池电解质的离子电导率高,制备的固态电池循环性能优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a composite solid-state sodium battery electrolyte and a preparation method thereof, and the preparation raw materials comprise NASICON powder, PCN-224 and potassium antimony tartrate, and the composite solid-state sodium battery electrolyte is obtained by mixing the preparation raw materials, ball milling and heat treatment. By introducing PCN-224 and potassium antimony tartrate into the NASICON powder matrix, the ionic conductivity of the composite solid-state sodium battery electrolyte can be significantly improved, and the battery performance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state battery technology, specifically relating to a composite solid-state sodium battery electrolyte and its preparation method. Background Technology

[0002] Sodium superionic conductor (NASICON, typically composed of Na3Zr2Si2PO4) 12 Due to its high ionic conductivity, good chemical stability, and low cost, sodium-based electrolytes have become an important candidate material for solid-state batteries. However, the sintering temperature of NASICON ceramic electrolytes is relatively high, which easily leads to sodium volatilization. Furthermore, they have high grain boundary resistance and poor interfacial compatibility with sodium metal anodes, limiting their application. Summary of the Invention

[0003] The purpose of this invention is to provide a composite solid sodium battery electrolyte and its preparation method. By introducing PCN-224 and potassium antimony tartrate into NASICON raw materials, the ionic conductivity of the composite solid sodium battery electrolyte is significantly improved, thereby enhancing battery performance.

[0004] To achieve the above objectives, the present invention provides the following technical solution: The composite solid sodium battery electrolyte is prepared using raw materials including NASICON powder, PCN-224, and potassium antimony tartrate.

[0005] In a preferred embodiment of the present invention, by adding PCN-224, it is thermally decomposed into a carbonaceous / Zr oxide composite with a porous structure during heat treatment, which can serve as a fast channel for mass transport, promote uniform diffusion of elements during sintering, and reduce grain boundary resistance.

[0006] In a preferred embodiment of the invention, potassium antimony tartrate is added to provide Sb and K sources during heat treatment. The Sb source enters the crystal lattice, optimizing the crystal structure and enhancing the Na+ content. + Mobility; the K source forms a low-melting-point liquid phase at high temperature, which promotes liquid phase sintering, reduces densification temperature, and fills grain boundary voids.

[0007] As a further improvement of the present invention, the mass fraction of NASICON powder in the raw materials is 88~93 wt%, preferably 89~92 wt%, and even more preferably 89.5~90.5 wt%.

[0008] As a further improvement of the present invention, the mass fraction of PCN-224 in the raw materials is 2.0~5.0 wt%, preferably 3.0~4.5 wt%, and even more preferably 3.5~4.5 wt%.

[0009] As a further improvement of the present invention, the mass fraction of potassium antimony tartrate in the raw materials is 0.5~2.5 wt%, preferably 1.5~2.0 wt%, and even more preferably 1.5~1.8 wt%.

[0010] As a further improvement of the present invention, the raw materials for preparation also include at least one of fluoride salts and sodium supplements.

[0011] As a further improvement of the present invention, the mass ratio of PCN-224 to fluoride salt in the raw materials is 1~4:1.

[0012] As a further improvement of the present invention, the mass ratio of sodium supplement to potassium antimony tartrate in the raw materials is 1.5~4:1.

[0013] As a further improvement of the present invention, the fluoride salt is selected from at least one of sodium fluoride and sodium tetrafluoroborate.

[0014] As a further improvement of the present invention, the sodium supplement is selected from at least one of sodium oxalate, sodium gluconate, and disodium oxalate.

[0015] As a further improvement of the present invention, the mass fraction of fluoride salt in the raw materials is 1.0~3.0 wt%, preferably 1.5~2.5 wt%, and more preferably 2.0~2.5 wt%.

[0016] As a further improvement of the present invention, the mass fraction of sodium supplement in the raw materials is 1.0~4.0 wt%, preferably 2.0~3.0 wt%, and more preferably 2.0~2.5 wt%.

[0017] As a further improvement of the present invention, the fluoride salt is sodium fluoride.

[0018] As a further improvement of the present invention, the sodium supplement is sodium oxalate.

[0019] As a further improvement of the present invention, the particle size D50 of the NASICON powder is 1~3 μm.

[0020] As a further improvement of the present invention, the raw materials for preparing the composite solid sodium battery electrolyte include the following components in mass fractions: 88~93 wt% NASICON powder, 2.0~5.0 wt% PCN-224, 0.5~2.5 wt% potassium antimony tartrate, 1.0~3.0 wt% sodium fluoride and 1.0~4.0 wt% sodium oxalate.

[0021] As a further improvement of the present invention, the raw materials for preparing the composite solid sodium battery electrolyte include the following components in mass fractions: 89~92 wt% NASICON powder, 3.0~4.0 wt% PCN-224, 1.5~2.0 wt% potassium antimony tartrate, 1.5~2.5 wt% sodium fluoride and 2.0~3.0 wt% sodium oxalate.

[0022] As a further improvement of the present invention, the raw materials for preparing the composite solid sodium battery electrolyte include the following components in mass fractions: 89.5~90.5 wt% NASICON powder, 3.5~4.5 wt% PCN-224, 1.5~1.8 wt% potassium antimony tartrate, 2.0~2.5 wt% sodium fluoride and 2.0~2.5 wt% sodium oxalate.

[0023] This invention also provides a method for preparing the composite solid-state sodium battery electrolyte as described in any of the above claims, comprising the following steps: The raw materials were mixed and then ball-milled to obtain the precursor; The precursor is subjected to heat treatment to obtain the composite solid sodium battery electrolyte.

[0024] As a further improvement of the present invention, the mixing process includes: PCN-224, potassium antimony tartrate, fluoride salts and sodium supplements were dispersed in an ethanol solution, and then NASICON powder was added and stirred until homogeneous.

[0025] As a further improvement of the present invention, the ethanol solution is an anhydrous ethanol solution.

[0026] As a further improvement of the present invention, the ball milling process includes a ball-to-material ratio of 2 to 4:1.

[0027] As a further improvement of the present invention, the ball milling process includes a rotation speed of 300~500 rpm.

[0028] As a further improvement of the present invention, the ball milling process includes a ball milling time of 2 to 6 hours.

[0029] As a further improvement of the present invention, the grinding balls used in the ball milling process are zirconium oxide grinding balls.

[0030] As a further improvement of the present invention, the ball milling process includes a vacuum drying process.

[0031] As a further improvement of the present invention, the temperature of the vacuum drying process is 70~90℃.

[0032] As a further improvement of the present invention, the vacuum drying process takes 10 to 14 hours.

[0033] As a further improvement of the present invention, the heat treatment process includes: Increase the temperature to 300-1300℃ at a rate of 1-6℃ / min and hold for 1-20 hours.

[0034] As a further improvement of the present invention, the heat treatment process includes: First, raise the temperature to 400-500℃ at a rate of 1-3℃ / min, and hold for 1-3 hours; Then raise the temperature to 600-700℃ at a rate of 2-5℃ / min and hold for 2-4 hours; Finally, increase the temperature to 1100-1300℃ at a rate of 3-6℃ / min and hold for 8-12 hours.

[0035] As a further improvement of the present invention, the heat treatment is carried out in an inert gas atmosphere.

[0036] As a further improvement of the present invention, the inert gas atmosphere includes a nitrogen or argon gas atmosphere.

[0037] As a further improvement of the present invention, the preparation method includes the following steps: S1. PCN-224, potassium antimony tartrate, sodium oxalate and sodium fluoride are added to anhydrous ethanol at a solid-liquid ratio of 1g:8~10mL. After ultrasonic dispersion, NASICON powder is added and stirred evenly to obtain a mixture. The mixture was ball-milled at a ball-to-material ratio of 2-4:1, at a speed of 300-500 rpm for 2-6 hours. After discharge, the mixture was dried to obtain precursor powder.

[0038] S2, Heat Treatment The precursor powder is pressed into shape and then subjected to heat treatment. The heat treatment process includes: First, raise the temperature to 400-500℃ at a rate of 1-3℃ / min, and hold for 1-3 hours; Then raise the temperature to 600-700℃ at a rate of 2-5℃ / min and hold for 2-4 hours; Finally, the temperature is increased to 1100-1250℃ at a rate of 3-6℃ / min, and held for 8-12 hours. The composite solid sodium battery electrolyte was obtained by cooling it in the furnace.

[0039] The present invention has at least the following technical effects: By adding PCN-224, potassium antimony tartrate, fluoride salts, and sodium supplements, combined with an optimized heat treatment process, the performance of the NASICON electrolyte was optimized. The pyrolysis of PCN-224 forms a porous carbonaceous / Zr oxide structure, promoting mass transport and uniform element diffusion; potassium antimony tartrate provides an Sb source to optimize the crystal structure, while the K source aids melting and lowers the sintering temperature; fluoride salts achieve fluorine substitution and grain boundary modification, enhancing ion conductivity; sodium oxalate decomposes to supplement the sodium source and assist in the formation of interconnected pore structures. The resulting composite solid-state sodium battery electrolyte exhibits high ionic conductivity, and the prepared solid-state battery demonstrates excellent cycle performance. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, and not all embodiments.

[0041] Therefore, the following detailed description of embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0042] Example 1 This embodiment provides a composite solid-state sodium battery electrolyte, the raw materials of which include the following components by mass fraction: NASICON powder (Na3Zr2Si2PO4). 12 92 wt% (D50=2 μm), 3 wt% PCN-224, 1.5 wt% potassium antimony tartrate, 1.5 wt% sodium fluoride and 2 wt% sodium oxalate.

[0043] This embodiment also provides a method for preparing a composite solid-state sodium battery electrolyte, including the following steps: S1. PCN-224, potassium antimony tartrate, sodium fluoride and sodium oxalate were added to anhydrous ethanol at a solid-liquid ratio of 1g:10mL. After ultrasonic dispersion for 45 min, NASICON powder was added and stirred evenly to obtain a mixture. The mixture was transferred to a planetary ball mill, zirconia grinding balls were added at a ball-to-material ratio of 3:1, the milling speed was 400 rpm, and the mixture was milled for 4 hours. After discharge, the mixture was vacuum dried at 80°C for 12 hours to obtain precursor powder.

[0044] S2, Heat Treatment The precursor powder was sieved through a 200-mesh sieve, pressed into a green body under a pressure of 300 MPa, and then heat-treated in an argon atmosphere in a tube furnace. The heat treatment procedure was as follows: First, raise the temperature to 450℃ at a rate of 2℃ / min and hold for 2 hours; Then increase the temperature to 650℃ at a rate of 3℃ / min and hold for 3 hours; Finally, the temperature is increased to 1250℃ at a rate of 5℃ / min and held for 10 hours. The composite solid sodium battery electrolyte was obtained by cooling it in the furnace.

[0045] Example 2 The difference between this embodiment and Embodiment 1 is that: The raw materials were adjusted to: 90 wt% NASICON powder, 4 wt% PCN-224, 1.5 wt% potassium antimony tartrate, 2.5 wt% sodium fluoride and 2 wt% sodium oxalate.

[0046] Example 3 The difference between this embodiment and Embodiment 1 is that: The raw materials were adjusted to: 93 wt% NASICON powder, 2.5 wt% PCN-224, 1 wt% potassium antimony tartrate, 1 wt% sodium fluoride and 2.5 wt% sodium oxalate.

[0047] Example 4 The difference between this embodiment and Embodiment 1 is that: The raw materials were adjusted to: 91 wt% NASICON powder, 3 wt% PCN-224, 2 wt% potassium antimony tartrate, 1.5 wt% sodium fluoride and 2.5 wt% sodium oxalate.

[0048] Example 5 The difference between this embodiment and Embodiment 1 is that: The raw materials were adjusted to: 89 wt% NASICON powder, 4 wt% PCN-224, 1.5 wt% potassium antimony tartrate, 2.5 wt% sodium fluoride and 3 wt% sodium oxalate.

[0049] Example 6 The difference between this embodiment and Embodiment 1 is that: The raw materials were adjusted to: 93 wt% NASICON powder, 2.5 wt% PCN-224, 1 wt% potassium antimony tartrate, 2 wt% sodium fluoride and 1.5 wt% sodium oxalate.

[0050] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: Potassium antimony tartrate is not included in the raw materials used for preparation, and sodium oxalate is adjusted to 3.5 wt%.

[0051] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: The raw materials used in the preparation do not include PCN-224 and are adjusted to: 92 wt% NASICON powder, 1.5 wt% potassium antimony tartrate, 4.5 wt% sodium fluoride and 2 wt% sodium oxalate.

[0052] Comparative Example 3 The difference between this comparative example and Example 1 is as follows: Sodium fluoride is not included in the raw materials used for preparation, and PCN-224 is adjusted to 4.5 wt%.

[0053] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: Sodium oxalate is not included in the raw materials used for preparation, and PCN-224 is adjusted to 5 wt%.

[0054] Comparative Example 5 The difference between this comparative example and Example 1 is as follows: The heat treatment procedure in step S2 is replaced with: The temperature was increased to 1250℃ at a rate of 5℃ / min and held for 10 hours.

[0055] Comparative Example 6 The difference between this comparative example and Example 1 is as follows: The heat treatment procedure in step S2 is as follows: First, raise the temperature to 450℃ at a rate of 10℃ / min and hold for 0.5 h; Then increase the temperature to 1250℃ at a rate of 10℃ / min and hold for 10 hours.

[0056] The composite solid sodium battery electrolytes prepared in Examples 1-6 and Comparative Examples 1-6 were sprayed with a dense layer of silver on both sides as blocking electrodes. The ionic conductivity of the ceramic sheet was tested by AC impedance method at a test temperature of 25℃. The results are shown in Table 1.

[0057] Table 1. Test results of electrolyte performance in composite solid-state sodium batteries

[0058] The composite solid-state sodium battery electrolytes prepared in Examples 1-6 and Comparative Examples 1-6 were assembled into all-solid-state sodium-ion batteries, and their performance was tested.

[0059] Assembly method: A metallic sodium sheet is attached to one side of the electrolyte in a composite solid-state sodium battery to obtain the electrolyte and the negative electrode. Sodium vanadium phosphate powder, conductive carbon black, and polyvinylidene fluoride are weighed and dispersed in an N2O substrate at a mass ratio of 90:5:5. The positive electrode slurry was prepared by stirring methylpyrrolidone until homogeneous. The slurry was then evenly coated onto aluminum foil and vacuum dried at 80°C for 12 hours. The foil was then formed into small round discs with a diameter of 14 mm using a die-casting machine, thus obtaining the positive electrode sheet. The positive electrode and an electrolyte sheet with a sodium foil attached were assembled into a battery and sealed. Cycle life tests were conducted at 25°C with a test voltage of 2.0–3.9 V and a 0.1C rate for 100 cycles. The test results are shown in Table 2.

[0060] Table 2 Cycle performance test results of all-solid-state sodium-ion batteries

[0061] The results showed that the electrolyte ionic conductivity, discharge specific capacity, and capacity retention of the prepared batteries were all within the optimal range in Examples 1-6.

[0062] Comparative Example 1 lacks potassium antimony tartrate, which results in a lack of Sb source lattice optimization and K source fluxing effect, leading to a decrease in densification, an increase in grain boundary resistance, and a decrease in electrolyte performance.

[0063] Comparative Example 2 lacks PCN-224, resulting in a missing porous structure, discontinuous material transport channels, decreased uniformity of element distribution at grain boundaries, insufficient density, and obstructed ion transport channels.

[0064] Comparative Example 3 lacks sodium fluoride, fluorine substitution, and the absence of grain boundary conductive phases, resulting in increased grain boundary resistance and Na... + Decreased mobility, increased interfacial impedance, decreased electrochemical stability, and accelerated battery cycle degradation.

[0065] Comparative Example 4 lacks sodium oxalate, resulting in insufficient compensation for sodium volatilization. Na loss during sintering leads to an increase in lattice defects. At the same time, the lack of decomposition gas-assisted pore formation results in unconnected pore structures, deterioration of interfacial chemical stability, and increased interfacial impedance.

[0066] Comparative Example 5 uses a single-stage heating program. The rapid decomposition of PCN-224 leads to uneven distribution of carbonaceous / Zr oxides. Potassium antimony tartrate and sodium oxalate decompose too quickly, resulting in gas escape. The grain size distribution becomes wider, the porosity is high and unevenly distributed, the ion conduction path is discontinuous, and the battery performance is significantly reduced.

[0067] In Comparative Example 6, the rapid heating rate caused potassium antimony tartrate, sodium fluoride, and sodium oxalate to decompose quickly, disrupting the uniformity of the microstructure and preventing the full formation of the porous structure. The rapid heating also led to the generation of thermal stress cracks and deterioration of the electrolyte performance.

[0068] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A composite solid-state sodium battery electrolyte, characterized in that, The raw materials for preparation include NASICON powder, PCN-224, potassium antimony tartrate, sodium fluoride and sodium oxalate; The raw materials used in the preparation contain 88-93 wt% NASICON powder, 2.0-5.0 wt% PCN-224, 0.5-2.5 wt% potassium antimony tartrate, 1.0-3.0 wt% sodium fluoride, and 1.0-4.0 wt% sodium oxalate.

2. The composite solid-state sodium battery electrolyte according to claim 1, characterized in that, The mass ratio of PCN-224 to sodium fluoride in the raw materials used for preparation is 1~4:1; And / or, the mass ratio of sodium oxalate to potassium antimony tartrate in the raw materials for preparation is 1.5~4:

1.

3. The method for preparing the composite solid-state sodium battery electrolyte according to any one of claims 1 to 2, characterized in that, Includes the following steps: The raw materials were mixed and then ball-milled to obtain the precursor; The precursor is subjected to heat treatment to obtain the composite solid sodium battery electrolyte.

4. The preparation method according to claim 3, characterized in that, The ball milling process includes: The ball-to-material ratio is 2~4:1; And / or, the rotational speed is 300~500 rpm; And / or, the ball milling time is 2~6 hours.

5. The preparation method according to claim 3, characterized in that, The heat treatment process includes: Increase the temperature to 300-1300℃ at a rate of 1-6℃ / min and hold for 1-20 hours.

6. The preparation method according to claim 3, characterized in that, The heat treatment process includes: First, raise the temperature to 300-500℃ at a rate of 1-3℃ / min, and hold for 1-3 hours; Then raise the temperature to 600-700℃ at a rate of 2-5℃ / min and hold for 2-4 hours; Finally, increase the temperature to 1000-1300℃ at a rate of 3-6℃ / min and hold for 8-12 hours.

7. The preparation method according to claim 3, characterized in that, The heat treatment is carried out in an inert gas atmosphere.

Citation Information

Patent Citations

  • Method for preparing NASICON type solid electrolyte material through doping modification

    CN118993078A

  • Solid-state battery having a hybrid capacitor material with a metal-organic framework

    US20220140422A1